2019
DOI: 10.3389/fonc.2019.00650
|View full text |Cite
|
Sign up to set email alerts
|

The Lethality of [Pazopanib + HDAC Inhibitors] Is Enhanced by Neratinib

Abstract: Sarcomas are a diverse set of malignancies. For soft tissue sarcomas, the kinase and chaperone inhibitor pazopanib is a standard of care therapeutic. Previously, we demonstrated that HDAC inhibitors enhanced pazopanib lethality against sarcoma and other tumor cell types in vitro and in vivo . The present studies defined mechanisms of drug-combination resistance. Exposure of sarcoma and PDX ovarian carcinoma cells to [pazopanib + entinostat] caused a prolonged activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…All cell lines were cultured at 37°C (5% (v/v CO 2 ) in vitro using RPMI supplemented with 5% (v/v) fetal calf serum and 10% (v/v) non-essential amino acids. Cells were transfected with siRNA molecules or plasmids as described in prior manuscripts ( 7 10 ). Cells were transfected with plasmids (0.1 μg) using lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cell lines were cultured at 37°C (5% (v/v CO 2 ) in vitro using RPMI supplemented with 5% (v/v) fetal calf serum and 10% (v/v) non-essential amino acids. Cells were transfected with siRNA molecules or plasmids as described in prior manuscripts ( 7 10 ). Cells were transfected with plasmids (0.1 μg) using lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…In the past 5 years the multi-kinase and chaperone inhibitor pazopanib was FDA approved for treatment of the majority of STS subtypes ( 6 ). Pazopanib, alone or in combination with other agents in our hands utilizes endoplasmic reticulum stress signaling and autophagosome formation as key components of its mechanisms of action ( 7 10 ). In preliminary studies for this manuscript initially we examined whether pazopanib and 602 could interact to kill sarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…189,190 For example, HDAC inhibitors enhanced the anti-cancer effect of pazopanib against sarcoma cells, and this effect was even more pronounced in combination with the TK inhibitor, neratinib. 191,192 Furthermore, results from a phase I clinical trial found panobinostat to increase the efficacy of the topoisomerase II inhibitor epirubicin (PubChem CID: 41867) and this led to clinical benefit and has the potential to reverse anthracycline resistance. 193 Interestingly, tazemetostat (PubChem CID: 66558664), a lysine methyltransferase inhibitor of the histone modification enzyme enhancer of zeste homolog 2 (EZH2), was approved by the FDA in 2020 as the first epigenetic therapy for solid tumors and is used to treat advanced or metastatic epithelioid sarcoma.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…For instance, neratinib (ERBB1/2/4 inhibitor) enhanced [pazopanib (the kinase inhibitor) + entinostat (histone deacetylase inhibitor)] lethality against sarcoma and other tumor cell types in vitro and in vivo. Specifically, the triplet combination increases the phosphorylation of YAP/TAZ and promotes the conversion of LC3 and expression of Beclin1 and ATG13, which together enhance autophagosome formation 114,115 . The mammalian STK 26/ MST4 stimulates ATG4B activity and increases autophagic flux by phosphorylating ATG4B 116 .…”
Section: Cancermentioning
confidence: 99%